Inferior Olivary Nucleus Involvement in Pediatric Neurodegenerative Disorders: Does It Play a Role in Neuroimaging Pattern-Recognition Approach? - Mirabelli-Badenier, Marisol; Morana, Giovanni; Bruno, Claudio; Di Rocco, Maja; Striano, Pasaquale; De Grandis, Eusa; Veneselli, Edvige; Rossi, Andrea; Biancheri, Roberta (Neuropediatrics, 2015)
The diagnostic work up of neurometabolic/degenerative disorders is complex. In such context, identification of neuroradiological features suggestive of specific diagnoses is useful to prompt further diagnostic tests. Involvement of the inferior olivary nucleus (ION) has been reported in several pathologic conditions, either as a primary manifestation of disease or secondary to hypertrophic olivary degeneration (HOD). In this study, we analyzed a cohort of 95 children with different neurometabolic/degenerative diseases involving the brainstem and cerebellum, with the aim to evaluate whether ION involvement plays a role in a neuroimaging-based pattern-recognition approach. A total of 13 patients (13.7%) showed bilateral high-signal intensity and enlargement of the ION on T2-weighted images, while 16 (16.8%) had ION T2-hyperintensity without olivary nucleus enlargement. Our study demonstrates that ION involvement is not rare in children with neurometabolic/degenerative disorders. Two main neuroradiological patterns, that is, “T2-hyperintense signal” and “T2-hyperintense signal with enlargement” are found. These patterns can be related to different etiologies, and do not suggest specific diagnoses. Primary ION lesion can be characterized by olivary swelling, and the differentiation from typical secondary HOD may be difficult.
Keywords: inferior olivary nucleus; neurodegenerative disorders; magnetic resonance imaging; hypertrophic olivary degeneration